The Reliability and Agreement of the Fibromyalgia Survey Questionnaire in an Italian Sample of Obese Patients - Varallo, Giorgia; Ghiggia, Ada; Arreghini, Marco; Capodaglio, Paolo; Manzoni, Gian Mauro; Giusti, Emanuele Maria; Castelli, Lorys; Castelnuovo, Gianluca (Frontiers in Psychology, 2021)
The Fibromyalgia Survey Questionnaire (FSQ) was self-administered by a sample of 207 Italian individuals with obesity to screen for fibromyalgia (FM). We aimed to investigate the inter-rater reliability and the agreement in the detection of FM symptomatology between the self-administered FSQ and the clinical interview conducted by a rheumatologist. All the patients were divided randomly into two groups (group A and group B): a rheumatologist first interviewed patients of the group A and after 48 hours, the patients completed the self-report FSQ. Patients of group B first completed the FSQ and 48 hours later were interviewed by a rheumatologist. The agreement between the measurements was good with the Bland-Altman analysis showing low bias scores for the two subscales of the FSQ. Results showed that 33% of the sample satisfied the criteria for a diagnosis of fibromyalgia. The FSQ is a self-reporting measure that showed substantial reliability providing fast screening for FM symptomatology.